IMPLEMENTATION OF THE VILLAGE FUND POLICY BASED ON MINISTER OF FINANCE REGULATION NUMBER 93 OF 2015 IN SUB-DISTRICT ‘’X’’ - JAMES PELUPESSY (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
This research aims to describe the policy implementation and inhibiting factors of the Village Fund implementation. This research uses a descriptive-qualitative approach. Data collection was conducted through literature study, documentation, and digital internet searching. The results of this study indicate that the implementation of village funds in Sub-district X, Regency Y has been running in accordance with the Minister of Finance Regulation No. 93/2015 on the procedures for allocation, distribution, use, monitoring, and evaluation. However, at the distribution stage there was a delay from the predetermined date. The inhibiting factors in the implementation of the Village Fund are delays in making Technical Guidelines (Juknis) and also the quality of human resources.